2021
DOI: 10.31254/jsir.2021.10101
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Micropropagation of Rose (Hybrid Rosa spp.) through Plant Tissue Culture Technique

Abstract: Roses are the most important cut flowers in the world. Tissue culture of rose has been improved since last twenty years, and exploited for various purposes from basic anatomical and physiological research to micropropagation from auxiliary buds, shoot tips, leaf explants, etc. Single bud nodal stem segments were surface sterilized and then cultured on MS medium supplemented with 30 g/l sugar, 6 g/l agar and different concentrations of BAP(1, 2, 3, 4 and 5mg/l). Among them, the most suitable concentration for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…It was found that increasing BAP concentrations up to 3.0 mg/l improved the percentage of shoot proliferation (88%), with an average of 7.20 ± 0.80 regenerated shoots per culture and a mean length of 5.22 ± 0.47 cm (Table 4). These findings are consistent with the findings of Oo et al (2021) and Thi (2008) in the case of R. hybrida. They showed that MS medium supplemented with 3.0 mg/l BAP was found to be the optimum concentration for shoot proliferation.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…It was found that increasing BAP concentrations up to 3.0 mg/l improved the percentage of shoot proliferation (88%), with an average of 7.20 ± 0.80 regenerated shoots per culture and a mean length of 5.22 ± 0.47 cm (Table 4). These findings are consistent with the findings of Oo et al (2021) and Thi (2008) in the case of R. hybrida. They showed that MS medium supplemented with 3.0 mg/l BAP was found to be the optimum concentration for shoot proliferation.…”
Section: Resultssupporting
confidence: 93%
“…Additionally, the results indicate that the single use of IBA performed significantly better than NAA and the combined effect of IBA and NAA on the rooting of micro-shoots. As opposed to this, Oo et al (2021) demonstrated substantial rooting in hybrid Rosa spp. on half-strength MS medium containing 15 g/l sugar and 1.0 mg/l NAA.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation